PENGARUH BRAND IMAGE DAN KUALITAS PRODUK BITTERSWEET BY NAJLA TERHADAP KEPUASAN KONSUMEN PADA FOLLOWERS INSTAGRAM @BITTERSWEET_BY_NAJLA - Putri Dewa Agustin; Ahmad Yazid Lubis (Jurnal Sosial Humaniora dan Pendidikan, 2023)
Food is one of the basic human needs. Bittersweet By Najla is a food and beverage industry that has pioneered a successful dessert box business in Indonesia. This research aims to determine the influence of the brand image and product quality of Bittersweet By Najla on consumer satisfaction among the followers of the Instagram account @bittersweet_by_najla. The method used in this research is a quantitative method using the uses and effect theory. The sampling technique employed is purposive sampling, with the Slovin formula resulting in a sample size of 400 respondents. The multiple linear regression results and the F-test show that the variables of brand image and product quality have a positive and significant impact on consumer satisfaction, with regression coefficients of X1 at 0.122 and X2 at 0.366. The F-test result is less than 0.05, leading to the rejection of the null hypothesis (Ho) and the acceptance of the alternative hypothesis (Ha). This indicates that the brand image and product quality of Bittersweet By Najla influence consumer satisfaction among the followers on Instagram @bittersweet_by_najla.